A Simple Identification Strategy for Gary Becker's Time Allocation Model - Laurens Cherchye; Bram De Rock; Frederic Vermeulen (Institute for the Study of Labor (IZA), 2015)
The implementation of Gary Becker's (1965) time allocation model is hampered by the fact that values of the different time uses are usually not observed. In practice, one often assumes that the value of time is uniform across time uses by using market wages. This approach implies a fundamental identification problem. We demonstrate that the identification problem can be solved if production shifters are available.
Keywords: D11; D12; D13; 330; time use; home production; identification; production shifter